Froggy plays soccer - London, Jonathan, 1947-; Remkiewicz, Frank (New York : Puffin, 2001)
Froggy is very excited when his Dream Team plays for the city soccer championship, but he makes a mistake on the field that almost costs the team the game.
Elem. School Library Collection.
School Library Journal.
Wilson's Children.
2.0.
2.0
K-3
Keywords: Animals -- Fiction; Froggy (Fictitious character) -- Fiction; Frogs -- Fiction; Soccer -- Fiction; Animals -- Fiction; Froggy (Fictional character) -- Fiction; Frogs -- Fiction; Soccer -- Fiction